Tumor/Stromal Caveolin-1 Expression Patterns in Pleural Mesothelioma Define a Subgroup of the Epithelial Histotype With Poorer Prognosis. Issue 6 (1st June 2014) - Righi, Luisella; Cavallo, Maria Cristina; Gatti, Gaia; Monica, Valentina; Rapa, Ida; Busso, Simone; Albera, Carlo; Volante, Marco; Scagliotti, Giorgio V.; Papotti, Mauro
Abstract: Objectives: Malignant pleural mesothelioma (MPM) is a highly aggressive disease for which new prognostic biomarkers need to be identified. Caveolin-1 (CAV1), the most important member of caveolae, has been described as deregulated in MPM at the genomic level, but detailed histologic information on its distribution and prognostic role is still lacking. Methods: A series of 131 MPMs (91 epithelial, 17 biphasic, and 23 sarcomatous histotype) were investigated for CAV1 expression with immunohistochemistry and correlated with clinical-pathologic variables and outcome. Results: CAV1 was detected in neoplastic cells of 70 (77%) of 91 epithelial, 17 (100%) of 17 biphasic, and 23 (100%) of 23 sarcomatous MPMs. Furthermore, in the epithelial group, CAV1 expression in spindle-shaped stromal cells was detected in 61 (67%) of 91 cases. Conclusions: The presence of stromal CAV1 expression was associated with a worse patient outcome. In MPM, CAV1 is differentially expressed according to low- to high-grade histotypes. Furthermore, in the MPM epithelial group, additional stromal CAV1 expression is associated with a worse prognosis.